Kansas River inventory - Calwell, Laura; Annett, Cynthia; Stephenson, R.J (Kansas State University, 2009)
Friends of the Kaw (FOK) is the only grassroots, environmental organization whose sole purpose is to protect and preserve the Kansas River. In 2001 Friends of the Kaw joined the international Waterkeeper Alliance, and as a condition of our Alliance membership, FOK maintains a full-time, professional Riverkeeper. A non-governmental public advocate, the Riverkeeper's job includes the roles of leader, educator, investigator, media spokesman, and scientist. Laura Calwell is the current Kansas Riverkeeper and principle investigator for this project. Unlike the Arkansas, Missouri, and other rivers of the Great Plains, the Kaw headwaters arise in the prairie, not the mountains, making it the longest prairie river in the world. The Kaw drains 53,000 square miles of a commercial agricultural region—36,000 square miles in Kansas (almost the entire northern half of the state), 11,000 square miles in Nebraska, and 6,000 square miles in Colorado. As a result, pesticide residues are found in streams and fish throughout the entire basin. Mercury, dieldrin, chlordane, PCBs, and other carcinogenic substances also contaminate fish and river waters. The Kansas Department of Health and Environment has issued an advisory limiting fish consumption (and barring any consumption for children and pregnant women). However, the river serves as fishing grounds for many low-income populations, including large numbers of Vietnamese, African-Americans, American Indians, and other minority groups. The Kaw needs help. During the past ten years, it has been listed as one of American Rivers' Most Endangered Rivers three times. The river suffers from non-compliant wastewater treatment systems located on its banks as well as illegal waste dumping, fills, and industrial discharges. Also, invasive species such as Asian carp and zebra mussels have been unintentionally introduced into the Kansas River basin with unknown consequences at this time. There are ten (10) permitted in-stream dredge sites in the Kansas River. In-stream sand dredging is an activity that causes great damages to riverbanks and bed morphology, and possibly destroys native fish and invertebrate habitat. The Army Corps of Engineers has recently retired three (3) permits (not reflected in the 10 active permits) due to unacceptable riverbed degradation in the Kaw. Friends of the Kaw was primarily responsible for the creation of a Technical Advisory Committee (TAC) to study bed and channel degradation on the Kaw authorized by the Kansas Water Authority in 2005. The Kansas Riverkeeper was appointed to this committee as a stakeholder along with representatives from state and federal agencies that have jurisdiction over the river. The need for comprehensive baseline information was identified by the TAC to make reliable and appropriate decisions. The state has committed funds to begin cross section surveys and aerial photo documentation of the entire river. To supplement this research FOK initiated our own research project to investigate sources of contaminants and river degradation, the Kaw River Inventory. The Inventory will provide information on the condition of the riparian vegetation along the banks of the Kaw and for all discharge pipes, physical structures, bank stabilization efforts, and areas in need of restoration with digital photos linked to GPS coordinates. Our goal is to compile the first publicly accessible, comprehensive inventory for the Kaw River in a web-based format. This assessment will address specific needs, define goals, and create and implement action plans for protection or restoration of the Kaw River watershed. The Kansas River Atlas is one of the most important services provided by the Friends of the Kaw to the general public in the Kansas River watershed (http://kansasriver.org ). The Inventory expands our activities from summarizing existing information, as is currently presented on the River Atlas, to collecting new data and formatting it for public use. In 2007, working with a group of volunteers, including several scientists, we collected data on 5 multi-day kayak excursions covering the entire 171 miles of the Kaw. The water level was high during most of the spring and summer of 2007. The raw data from the 2007 field season consists of over 500 photographs linked to GPS coordinates and accompanying written descriptions. During the summer of 2008, Laura Calwell, the Kansas Riverkeeper, Dr. Cynthia Annett, FOK’s scientific advisor, and R.J. Stevenson, an FOK board member and database advisor, kayaked the entire length of the Kaw during an eleven-day period, refining the data and assembling a set of GPS referenced photographs during a low water period. An overview of the methodology used for the Inventory can be found at http://cynthia.annett.googlepages.com/ksusustainabilityseminar
Keywords: Friends of the Kaw; Kansas River (Kan.); Kansas Riverkeeper